William Blake as natural philosopher, 1788-1795 - Fletcher, Joe (Anthem Press, 2022)
William Blake as Natural Philosopher, 1788-1795 takes seriously William Blake's wish to be read as a natural philosopher, particularly in his early illuminated works, and reveals the way that poetry and visual art were for Blake an imaginative way of philosophizing.